Answer:
p + q = (-2) --------(1)
p - q = 8 ----------(2)
<em><u>on</u></em><em><u> </u></em><em><u>s</u></em><em><u>i</u></em><em><u>m</u></em><em><u>p</u></em><em><u>l</u></em><em><u>i</u></em><em><u>f</u></em><em><u>y</u></em><em><u>i</u></em><em><u>n</u></em><em><u>g</u></em><em><u> </u></em><em><u>both</u></em><em><u> </u></em><em><u>equati</u></em>
8 + q = (-2)-q
q + q = (-2) -8
2q = (-10)
q = (-10)/2
q = (-5)
putting the value of q = (-5) in the equation
p + (-5) = (-2)
p = (-2)+5
p = 3
hence, p = 3 , q = (-5)
34
Step-by-step explanation:
2210 / 65 = 34. There is no further explanation
425